The representation of nature and man in metaphors of Aipin’s works - Abdyzhaparova, Marina; Fedosova, Tatyana; Kargapolov , Yevgeny (Revista EntreLinguas, 2022)
This study analyzes the metaphors in such works of contemporary Khanty writer as Yeremei Aipin “Khanty, or the Morning Star Dawn” and “Mother of God in the Bloody Snows”. The metaphors under study reflect the essence of interaction of man and nature and are presented by the author in the form of metaphorical schemes. As a result of the study, the conclusion is made that in the minds of the characters presented in the author’s works, nature and man have a close connection, which is reflected in the use of metaphors that correspond to iconic cognitive schemes: the source sphere “nature” – the target sphere “man”, the source sphere “man” – the target sphere “nature”. The results can be applied in the regional studies, in teaching such courses as “Linguistic Worldview of the Small-numbered Peoples”, and in the works devoted to the creative writing style of Ye.D. Aipin. Este estudio analiza las metáforas en obras del escritor contemporáneo de Khanty como Yeremei Aipin “Khanty, or the Morning Star Dawn” y “Mother of God in the Bloody Snows”. Las metáforas en estudio reflejan la esencia de la interacción del hombre y la naturaleza y son presentadas por el autor en forma de esquemas metafóricos. Como resultado del estudio se concluye que en la mente de los personajes presentados en las obras del autor, la naturaleza y el hombre tienen una estrecha conexión, lo que se refleja en el uso de metáforas que corresponden a esquemas cognitivos icónicos: la esfera fuente. “naturaleza” – la esfera de destino “hombre”, la esfera de origen “hombre” – la esfera de destino “naturaleza”. Los resultados se pueden aplicar en los estudios regionales, en la enseñanza de cursos como "Cosmovisión lingüística de los pueblos pequeños", y en los trabajos dedicados al estilo de escritura creativa de Ye.D. Aipín. Este estudo analisa as metáforas em obras do escritor contemporâneo Khanty como Yeremei Aipin “Khanty, or the Morning Star Dawn” e “Mother of God in the Bloody Snows”. As metáforas em estudo refletem a essência da interação do homem ...